Forecasting Malaysian Tourist Arrivals in Thailand from 2024 to 2027 using the Holt-Winters Method - Suwanvijit, Wassana (Emerging Advances in Integrated Technology, 2025)
This study employs the Holt-Winters method to forecast Malaysian tourist arrivals in Thailand from 2024 to 2027. Two approaches were compared: one utilizing monthly tourist data from 2013 to 2023 and the other excluding figures from 2020 to 2022 due to the COVID-19 pandemic's impact on tourist numbers. Evaluation metrics include Mean Absolute Scaled Error (MASE) and Mean Absolute Percentage Error (MAPE). The findings reveal that the second approach, accounting for the pandemic's effects, yields superior forecasting accuracy compared to the first. By excluding these abnormal years, the forecasting model can offer more accurate estimates by reducing the impact of temporary disturbances caused by the pandemic. This strategy improves the model's capacity to forecast future tourist arrivals with increased accuracy and certainty, aiding in strategic decision-making and resource allocation within the tourism sector.